VD_FINDINFO HC / 2019 / 569 vom 17. Juni 2019 - VD Tribunal cantonal (2019)
AVANCE DE FRAIS, DÉCISION D'IRRECEVABILITÉ, OBLIGATION DE CHIFFRER LES CONCLUSIONS | 101 al. 1 CPC (CH), 101 al. 3 CPC (CH), 59 al. 2 CPC (CH), 60 CPC (CH), 97 CPC (CH), 98 CPC (CH)